Extreme Events, Entrepreneurial Start-Ups, and Innovation: Theoretical Conjectures - Thomas Gries; Wim Naudé (Institute of Labor Economics (IZA), 2020)
In light of the COVID-19 pandemic, we scrutinize what has been established in the literature on whether entrepreneurship can cause and resolve extreme events, the immediate and long-run impacts of extreme events on entrepreneurship, and whether extreme events can positively impact (some) entrepreneurship and innovation. Based on this, we propose a partial equilibrium model to provide several conjectures on the impact of COVID-19 on entrepreneurship and derive policy recommendations for recovery. Our model's comparative statics shows that entrepreneurship recovery will benefit from aggregate demand-side support measures, combined with direct subsidies for start-ups, firms' revenue losses, and loan liabilities, as well as from actions that promote income redistribution.
Keywords: I18; L26; L53; M13; 330; entrepreneurship; innovation; COVID-19; extreme events; development